Review on Diabetic Complications and their Management by Flavonoids and Triterpenoids - Shivam; Gupta, Asheesh K.; Kumar, Sushil (Natural Products Journal, The, 2023)
Diabetes mellitus, together with its numerous consequences, is rapidly becoming a major health issue. Natural products are secondary metabolites found in plants that have a wide range of biological functions. The development of anti-diabetic medications derived from natural compounds, particularly those derived from plants having a documented folk-use history in the treatment of diabetes, is gaining traction. Many studies have shown the usefulness of natural flavonoids with hypoglycemic properties in the management of diabetic problems, along with their advantages. This paper describes the mechanisms of action of several natural flavonoids whose hypoglycemic effects have been confirmed. Comprehensive lifestyle treatments can help those at high risk of diabetes to avoid or delay the start of the disease, according to the results of randomized controlled trials. Terpenoids are a type of natural substance that have been identified as an anti-diabetic agent in various studies. Some of them are in various phases of preclinical and clinical testing to conclude whether they can be used as anti-diabetic drugs. These compounds can block the enzymes involved in insulin resistance, facilitate glucose metabolism, and positively affect plasma glucose and insulin levels. By blocking multiple pathways implicated in diabetes and its consequences, flavonoids and triterpenes can operate as potential agents in the treatment of diabetic retinopathy, neuropathy, and nephropathy, as well as poor wound healing. However, there have been few attempts to investigate the biological effects of triterpenes and clinical research investigating their use in the treatment of diabetes. As a result, it is critical to pay close attention to these chemicals' therapeutic potential and to contribute fresh information to the scientific community. This review focuses on current advancements in flavonoids and triterpenes chemistry, derivatives, biological interventions, and therapeutic applications, with a focus on diabetes and related illnesses.
Keywords: neuropathy